Using multimodal warning as a method of optimizing an in-vehicle warning system - Zuki, F.S.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
The use of multimodality in warning systems has proven to be more effective than any unimodal warning systems, as it lowers the visual workload and provides multiple channels in alerting users. Unfortunately, uni modality is found to be most commonly practiced in warning systems, instead. Literature suggests that audio and haptic multimodal warning systems is the most suitable to be implemented in in-vehicle warning systems. This paper discusses on the optimization of audio and haptic warning systems for fatigue drivers. Scenarios on different causes of fatigue while driving are drafted and possible responses to the causes are proposed. This paper also proposes a study to find the optimum values for the combination of levels presented in parameters of dB and Hz in order to optimize the fatigue driver warning systems. © 2016 IEEE.